The Influence of Tax Planning and Corporate Governance on Firm Value (Empirical Study on Consumer Goods Sector Companies Listed on Indonesia Stock Exchange in the period 2017 - 2020) - Armansyah, Rendy; Wahyudi, Imam (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study seeks to investigate the effects of tax planning, institutional shareholding, managerial shareholding, board independence, and audit assurance quality on firm valuation. Firm valuation is regarded as a fundamental indicator of corporate performance, as it reflects investors’ perceptions and the overall financial condition of the firm. The analysis is conducted on a sample of 27 consumer goods companies listed on the Indonesia Stock Exchange (IDX) over the 2017–2020 period. A quantitative approach with an associative research design is employed, utilizing panel data regression techniques carried out using EViews 9.0. The empirical findings indicate that institutional shareholding, board independence, and audit assurance quality have a positive and statistically significant impact on firm valuation. In contrast, tax planning and managerial shareholding are found to have no significant effect on firm valuation within the observed sector. Moreover, the results of the simultaneous significance test (F-test) demonstrate that all independent variables jointly influence firm valuation, accounting for approximately 83.78% of its total variation. Overall, the findings emphasize that effective corporate governance structures and credible audit practices play a critical role in strengthening firm valuation, particularly in the consumer goods industry.